Patchouli Oil Innovation in Making Peel-Off Masks to Inhibit Acne Bacteria - Elly Sufriadi; Tiara Novebrina; Syaifullah Muhammad; M. Dirhamsyah (Journal of Patchouli and Essential Oil Products, 2022)
One of the plants that produce essential oils is patchouli. Patchouli contains patchouli oil which has many benefits, including as an antibacterial, antioxidant, and can be used in perfume mixtures. In this study, patchouli oil was used in the manufacture of peel-off masks. This study aims to test the ability of peel off masks as antibacterial which can inhibit acne-causing bacteria. The results of this study are peel-off mask can inhibit the growth of acne-causing bacteria, namely Staphylococcus aureus. The clear zone formed is 11.8 mm, which indicates that the peel-off mask has a strong inhibitory power to inhibit the growth of acne-causing bacteria. Peel-off masks have a thick texture, white colour, and are easy to peel off when dry.  The results of this study provide information for the development of Peel-Off masks as antibacterial, especially for the cosmetic and health fields.